Uji toksisitas akut ekstrak rotan sel (Daemonorop melanochaetes Bl.) terhadap larva udang (Artemia Salina Leach) dengan metode brine shrimp lethality test (BSLT) - Athaillah, Athaillah; Maulida Lubis, Roqayyah; Chandra, Putra; Pangondian, Aswan; Rambe, Robiatun (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Cell rattan is very popular because it has properties in treating malaria, diabetes and also has appetite-stimulating properties. The chemical content of rattan consists of flavonoids, alcohol, triterpenoids, saponins and glycosides. Flavonoids consist of 15 carbon atoms with a C6-C3-C6 structure. In plants, flavonoids are bound to sugars in the form of flavonoid glycosides and aglycones. Research methods include making rattan extract using the maceration method, phytochemical screening, toxicity activity testing using the BSLT (Brine Shrimp Lethality Test) method and determining the LC50 value based on the probit value. The research results show that rattan extract contains secondary metabolite compounds, including steroids/triterpenoids, saponins, flavonoids, glycosides and alkaloids. The results of the toxicity activity test showed that the LC50 value was 322 ppm and was included in the toxic category.